Will they lead by example? Assessment of vaccination rates and attitudes to human papilloma virus in millennial medical students. (December 2017) - Afonso, Nelia; Kavanagh, Maurice; Swanberg, Stephanie; Schulte, Jeanne; Wunderlich, Tracy; Lucia, Victoria
Abstract Background Human papillomavirus (HPV) is the most common sexually transmitted infection in the United States. It is also well established that HPV viruses are responsible for a variety of cancers. Little is known about the prevailing knowledge and attitudes toward the HPV vaccine in our future healthcare providers, a majority of whom were among the first in the target age group to receive the vaccine; the same vaccine that they will in turn be expected to recommend to their patients. The aims of this pilot study were to examine the HPV vaccination rate among medical students and determine their knowledge about HPV and attitudes toward vaccination. Methods To aid in the development of an HPV educational intervention, a needs assessment survey was administered to discover medical students' knowledge and attitudes toward the HPV vaccine. All medical students at a Midwestern US medical school were invited to complete the survey. Results Two hundred fourteen of 390 medical students completed the survey with 44% having been previously vaccinated. Although 82% of all respondents believed they would recommend the vaccine to family and friends, only 40% felt knowledgeable about the vaccine and 40% felt comfortable counseling patients. More positive attitudes and better knowledge scores were found in fully vaccinated students compared to non-vaccinated students. Provider recommendation was strongly associated with HPV vaccination status. Conclusions This study revealed the unique perspectives of U.S. millennial medical students as the first group of future healthcare providers to have personally encountered the HPV vaccine. Overall, students' knowledge as well as their comfort level in counseling patients was lacking. This assessment has guided the development of targeted educational interventions to address knowledge gaps and prepare students to appropriately discuss the vaccine with patients and parents and help protect young people from life threatening cancers.